2020
DOI: 10.1177/0361198120908871
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and Molecular Characterizations of Tire Rubber Modified Asphalt Emulsion

Abstract: The aim of this study was to characterize the chemical, molecular, and rheological properties of different asphalt emulsions including a newly introduced tire-rubber modified asphalt emulsion (CRS-2TR). Three emulsions (CRS-2TR, CRS-2P, and CRS-2) and one asphalt rubber binder (AC20-5TR) were evaluated in this study. The superpave performance grade (PG), surface performance grade (SPG), and the multiple stress creep recovery (MSCR) test were conducted to evaluate the rheological properties of the binder residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Liu et al and Yu et al demonstrated that the dynamic modulus of asphalt emulisons was enhanced by the addition of waterborne epoxy resin and nanoscale polyurethane [8,9]. Sarkar et al found that the rutting indexes of tire-rubber modified asphalt emulsions is higher than that of unmodified asphalt emulsions [10]. Shirkavand et al found that the G' and G'' of Zhang et al J Infrastruct Preserv Resil (2021) 2:22 asphalt emulsions increase with the addition of nanoclay [11].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al and Yu et al demonstrated that the dynamic modulus of asphalt emulisons was enhanced by the addition of waterborne epoxy resin and nanoscale polyurethane [8,9]. Sarkar et al found that the rutting indexes of tire-rubber modified asphalt emulsions is higher than that of unmodified asphalt emulsions [10]. Shirkavand et al found that the G' and G'' of Zhang et al J Infrastruct Preserv Resil (2021) 2:22 asphalt emulsions increase with the addition of nanoclay [11].…”
Section: Introductionmentioning
confidence: 99%
“…El BBS es una prueba selectiva ya que determina la adhesión mecánica de los materiales ensayados según sus propiedades mecánicas y reológicas, y según la sensibilidad que posea el material a la tracción uniaxial y a la humedad. El BBS tiene la capacidad de diferenciar entre la susceptibilidad a la humedad en diferentes muestras de ligantes asfálticos con diversas propiedades f ísicas y químicas (Sarkar, Rahman, Elseifi, Mayeux, y Cooper, 2020).…”
Section: Introductionunclassified
“…Tire rubber-modified asphalt emulsion had better aging resistance than the conventional and polymer-modified asphalt emulsion. The rheological and moisture stability of tire rubber-modified asphalt emulsion had comparable or 2 of 16 better performance [11]. The microstructure and the dispersion of the polymer in the emulsified asphalt could be evaluated with confocal microscopy, with the influence of different polymer addition methods being assessed.…”
Section: Introductionmentioning
confidence: 99%